Pendekatan Praktis-Teologis Dalam Fondasi Pendidikan Kristiani - Indri Putri Purnama Harefa; Emilia Worihana; Sandra R. Tapilaha (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
This article discusses a practial theological approach in the foundations of Christian Education. Through descriptive analysis of related literature, this article explores how theological approaches are applied in the context of Christian Education. This paper has several objectives, namely: First, to describe theoretical studies of practial Theological approaches; secondly, explaining the practical implications of the theological foundations of Christian Religious education. The conclusion highlight the importance of applying Truth in everyday life as a Blibical foundation, as well as seeking definitive direction from general theological principles.